SCREENING OF SOME BRINJAL CULTIVARS FOR RESISTANCE TO SHOOT AND FRUIT BORER (LEUCINODES ORBONALIS GUENEE) - PAYAL DEVI; PREETI GAWDE; VIJAY KUMAR KOSHTA (The Bioscan, 2015)
Response of different brinjal genotypes against brinjal shoot and fruit borer (Leucinodes orbonalis Guenee.) was evaluated Indira Gandhi Krishi Viswavidyalaya, Raipur (Chhattisgarh) in Rabi summer season 2013. 18 eggplant entries/accessions were evaluated for resistance to shoot and fruit borer. Minimum mean infestation in fruits was found in genotype Punjab Sadabahar, 2010/ BRLVAR-3, 2010/BRLVAR-1, 2010/BRLVAR- 4 while maximum mean infestation in fruits was recorded in Swarnamani. The calyx diameter and fruit diameter was significantly positive association with fruit infestation. Greenish purple colour variety was the least preferred by fruit borers with fruit damage of 5.21 per cent and highest fruit damage (28.27%) was noticed on infested fruits in the variety of dark purple with white colour.